2013
DOI: 10.2174/22102892013040100182
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Antioxidant Activities of Noot. On HL-60 Human Leukemia Cells

Abstract: The family of Simaroubaceae is known to contain quassinoids, a group of compounds that have been reported to possess numerous biological activities such as anticancer and antimalarial activities. This study was carried out to evaluate the inhibition of HL-60 cells proliferation and antioxidant capacity of various extracts from Quassia borneensis, an unexplored indigenous Simaroubaceae plant from Sabah. The bark and root of Q.borneensis were extracted by Soxhlet and maceration in methanol and further partitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This plant is traditionally used to cure malaria. In the vitro study, it is found that the quassinoids and canthin-6-ones of Q. borneensis are susceptible to HL-60 leukemic cancer cell line and effectively inhibit the human erythrocytes infected with Chloroquine-Resistant Plasmodium berghei NK65 (Ghazali, Nuddin, Sabireen, Razali, & Ishak, 2013;Kamarulzaman, Ghazali, & Nuddin, 2015;Li, Ghazali, Razali, & Nuddin, 2015;Nuddin, Adam, & Hamzah, 2012;Wan Razali, Nuddin, Ishak, & Ghazali, 2015).…”
Section: Aligning Strategic Research Agenda With Sustainable Developm...mentioning
confidence: 99%
“…This plant is traditionally used to cure malaria. In the vitro study, it is found that the quassinoids and canthin-6-ones of Q. borneensis are susceptible to HL-60 leukemic cancer cell line and effectively inhibit the human erythrocytes infected with Chloroquine-Resistant Plasmodium berghei NK65 (Ghazali, Nuddin, Sabireen, Razali, & Ishak, 2013;Kamarulzaman, Ghazali, & Nuddin, 2015;Li, Ghazali, Razali, & Nuddin, 2015;Nuddin, Adam, & Hamzah, 2012;Wan Razali, Nuddin, Ishak, & Ghazali, 2015).…”
Section: Aligning Strategic Research Agenda With Sustainable Developm...mentioning
confidence: 99%